The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3171/2016.11.focus16414
|View full text |Cite
|
Sign up to set email alerts
|

Cervical arthroplasty: what does the labeling say?

Abstract: OBJECTIVE The aim of this paper was to comprehensively review each of the Food and Drug Administration (FDA)–approved labels of 7 total cervical disc replacements, assess the exact methodology in which the trial was conducted, and provide a broad comparison of these devices to allow each surgeon to determine which disc best suits his or her specific treatment goals based on the specific labels and not the studies published. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
1
12
0
2
Order By: Relevance
“…The cervical artificial disc as a motion‐preserving prosthesis was used for cervical disc arthroplasty from the 1970s. Over the past 20 years, with the rapid development of materials science and cervical biomechanics research, many different designed types (unconstrained, semi‐constrained, and constrained) and different materials (metal to metal, metal to plastic) cervical artificial disc prosthesis have emerged. Cervical disc arthroplasty could maintain the physiological mobility, anatomical disc space height and normal segmental alignment of the operated level.…”
Section: Introductionmentioning
confidence: 99%
“…The cervical artificial disc as a motion‐preserving prosthesis was used for cervical disc arthroplasty from the 1970s. Over the past 20 years, with the rapid development of materials science and cervical biomechanics research, many different designed types (unconstrained, semi‐constrained, and constrained) and different materials (metal to metal, metal to plastic) cervical artificial disc prosthesis have emerged. Cervical disc arthroplasty could maintain the physiological mobility, anatomical disc space height and normal segmental alignment of the operated level.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, la manufactura aditiva por láser, también cono-cida como LAM, por sus siglas en inglés, es una relativamente novedosa técnica para elaborar piezas metálicas de uso en cirugía y teniendo en cuenta los detalles específicos en su tratamiento, puede ser perfectamente utilizada para la creación de implantes discales (26,27) . Adicionalmente, la adición de aleación de titanio (ELI) ha demostrado ser el tipo que posee mayor límite de fatiga, siendo un material bioinerte, con excelente resistencia a la corrosión, que puesto en una superficie ósea crea una intercara cerámica bioinerte que permite un excelente anclaje al tejido óseo vecino (28) .…”
Section: Discussionunclassified
“…Existen en la actualidad cinco tipos de aleaciones de titanio de uso médico que varían entre sí por su contenido de impurezas como el nitrógeno, carbono, hidrógeno, hierro y oxígeno. El aluminio le brinda a la aleación la tendencia a estabilizar la fase alfa, mientras que el vanadio estabiliza la fase beta como se evidenció en nuestro estudio metalográfico; además, la delgada capa de óxido, compacta y adherente, estabiliza el material y bajo condiciones fisiológicas determina una velocidad de corrosión muy baja (28) .…”
Section: Discussionunclassified
“…[1][2][3] Currently, indications for CDA include patients with either single or two-level cervical myelopathy or radiculopathy, who have failed conservative treatment, with limited instability and decreased degree of kyphosis. [4][5][6][7][8][9][10] The initial Federal Drug and Administration (FDA) Investigation Device Exemption (IDE) trials demonstrated positive clinical outcomes of CDA compared to ACDF in patients with cervical myelopathy and/or radiculopathy. 5,6,9,[11][12][13][14][15] Additionally, long-term follow-up studies have demonstrated favorable results of arthroplasty, particularly in terms of pain, disability, neurological status and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%